1998 IEEE Radiation Effects Data Workshop. NSREC 98. Workshop Record. Held in Conjunction With IEEE Nuclear and Space Radiation
DOI: 10.1109/redw.1998.731477
|View full text |Cite
|
Sign up to set email alerts
|

Radiation characterisation of commercially available 1 Mbit/4 Mbit SRAMs for space applications

Abstract: This paper presents the radiation results of a ground test program carried out on seven commercially available lMbit / 4Mbit SRAMs. Heavy ion and proton single event effect (SEE) results together with CO60 total ionizing dose performance are presented for these spacecraft candidate types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The M65608 SRAM has been tested under heavy ions and proton beams by ESA. In particular, three test campaigns under proton beam were performed, they are denoted "ESA 1997" [18], "RADECS 2005" [19] and "TRAD 2013" [20]. The SEU cross section versus proton energy is given in Fig.…”
Section: B Seu From Edac Counter At 719 Km Altitudementioning
confidence: 99%
“…The M65608 SRAM has been tested under heavy ions and proton beams by ESA. In particular, three test campaigns under proton beam were performed, they are denoted "ESA 1997" [18], "RADECS 2005" [19] and "TRAD 2013" [20]. The SEU cross section versus proton energy is given in Fig.…”
Section: B Seu From Edac Counter At 719 Km Altitudementioning
confidence: 99%
“…The M65608 SRAM has been tested under heavy ions and proton beams by ESA. In particular, three test campaigns under proton beam were performed, they are denoted "ESA 1997" [7], "RADECS 2005" [8] and "TRAD 2013" [9]. The SEU cross section versus proton energy is given in Fig.…”
Section: Flight Datamentioning
confidence: 99%
“…This aspect is very important because of the correction applied to the laser cross section. Indeed, in [7], Poivey et al found the Hitachi A SRAM very sensitive to multiple-bit upsets (MBUs), especially MBUs in a single word. Since the laser spot is larger than the memory cell of this SRAM, the correction is very important for the highest energy values.…”
Section: B Seu Sensitivity Comparisonsmentioning
confidence: 99%